Exploring the potential of using augmented reality approach in cultural heritage system - Ismail, Ajune Wanis (Elsevier BV, 2009)
Nowadays, Augmented Reality (AR) has become well-accepted technology with realism as one of the major contribution in computer graphics. AR is a technology that superimposed virtual and real scene in the same space. This technology requires accurate registration between virtual and real world augmentation, be it geometric registration or illumination registration. Hence, a lot of efforts have been done to explore the elements in AR technology including features and challenging issues in AR that need to be highlighted in order to reconstruct AR system. In cultural heritage system, the accurate registration is important to produce realistic environment and to improve the user's experience. The culture heritage reconstruction is significance to preserve, protect and interpret our culture and history. This paper will present an overview on the potentials of AR approach in cultural heritage system that will improve the quality of the system.